1990
DOI: 10.1002/1097-0142(19900515)65:10<2344::aid-cncr2820651030>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Diet and stomach cancer incidence a case–control study in Turkey

Abstract: A case-control study of diet and stomach cancer was conducted in Ankara, Turkey, between December 1987 and March 1988. One hundred patients with adenocarcinoma of the stomach were matched with 100 control subjects according to age, sex, and residential area. A dietary questionnaire was administered to all subjects by one of the authors. Gastric cancer patients consumed less fresh fruit and yellow-green vegetables (P < 0.000~) and meats (P < 0.001), and more salted food (P < 0.001), condiments (P < o . o O O~) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0
1

Year Published

1992
1992
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(49 citation statements)
references
References 22 publications
2
46
0
1
Order By: Relevance
“…Duration of refrigerator use or freezer use was not associated with stomach cancer risk in the Netherlands Cohort Study, in contrast with the results of casecontrol studies performed in Europe or the USA, which rather consistently reported a decreased stomach cancer risk with long-term use of a refrigerator [2,5,9,16,18,38,54]. Three of the case-control studies did not find an association [15,44,47] and no other cohort study reported on this association.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Duration of refrigerator use or freezer use was not associated with stomach cancer risk in the Netherlands Cohort Study, in contrast with the results of casecontrol studies performed in Europe or the USA, which rather consistently reported a decreased stomach cancer risk with long-term use of a refrigerator [2,5,9,16,18,38,54]. Three of the case-control studies did not find an association [15,44,47] and no other cohort study reported on this association.…”
Section: Discussionmentioning
confidence: 65%
“…Overall, in the majority of case-control studies, positive associations were observed for (total) salt or sodium intake [2,3,33,34], consumption of salted fish, salted meat, pickles and soup [5,7,16,[34][35][36][37][38][39][40], adding salt to food at dinner [5,9,41], preference of salty foods [4,5,11,40,42]. The relative risks reported ranged from 1.5 to 6.7 for various measures of salt intake [14].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of patients with gastric cancer were men (62.3%) with a men/women ratio of 1.65 in our study. In another casecontrol study conducted in Turkey by Demirer et al (1990), 64% of patients with gastric cancer were men and 36% were women.…”
Section: Discussionmentioning
confidence: 97%
“…Various risk factors have been recognized such as helicobacter pylori (H pylori) infection, cured meat, smoking, and alcohol while Mediterranean diet, vegetables and fruits, vitamin C, retinol and high intake of cereal fiber decrease the risk of stomach cancer (Kolonel et al, 1981;Demirer et al, 1990;Schottenfeld and Fraumeni, 2006;Wang, 2009;Gonzalez and Riboli, 2010). An ecologic analysis in Brazil suggested that differences in living standards among populations probably have an important role in incidence differences (Koifman and Koifman, 1997).…”
Section: 1669 Correlation Of Cancer Incidence With Probable Risk Facmentioning
confidence: 99%